First line shape analysis and spectroscopic parameters for the ν11 band of 12C2H4. (November 2016) - Es-sebbar, Et-touhami; Mantzaras, John; Benilan, Yves; Farooq, Aamir
Abstract: An accurate knowledge of line intensities, collisional broadening coefficients and narrowing parameters is necessary for the interpretation of high-resolution infrared spectra of the Earth and other planetary atmospheres. One of the most promising spectral domains for 12 C2 H4 monitoring in such environments is located near the 3.36 µm window, through its ν11 C–H stretching mode. In this paper, we report an extensive study in which we precisely determine spectroscopic parameters of 12 C2 H4 ν11 band at 297±1 K, using a narrow Difference-Frequency-Generation (DFG) laser with 10 − 4  cm − 1 resolution. Absorption measurements were performed in the 2975–2980 cm − 1 spectral window to investigate 32 lines corresponding to J' Ka', Kc' ← J Ka, Kc, where, 5≤ J ≤7; 0≤ K a ≤6 and 1≤ K c ≤14. Spectroscopic parameters are retrieved using either Voigt or appropriate Galatry profile to simulate the measured 12 C2 H4 line shape. Line intensities along with self-broadening coefficients are reported for all lines. Narrowing coefficients for each isolated line are also derived. To our knowledge, the current study reports the first extensive spectroscopic parameter measurements of the 12 C2 H4 ν11 band in the 2975–2980 cm − 1 range. Highlights: Analysis of the 12 C2 H4 ν11 band in the 2975–2980 cm − 1 spectral window using laser absorption spectroscopy. Absolute line intensities and Self-broadening coefficients of 32 lines of the 12 C2 H4 ν11 band are measured accurately. Narrowing parameters of 32 transitions belonging to the 12 C2 H4 ν11 band are reported. Retrievals of spectroscopic parameters are performed using Voigt and Galatry profiles.